Dietary Creatine Supplementation in Gilthead Seabream (Sparus aurata) Increases Dorsal Muscle Area and the Expression of myod1 and capn1 Genes - Ramos-Pinto, Lourenço; Lopes, Graciliana; Sousa, Vera; Castro, L. Filipe C.; Schrama, Denise; Rodrigues, Pedro; Valente, Luísa M. P. (Frontiers in Endocrinology, 2019)
Creatine (Cr) is an amino acid derivative with an important role in the cell as energy buffer, that has been largely used as dietary supplement to increase muscle strength and lean body mass in healthy individuals and athletes. Yet, studies in fish are scarce. The aim of this work was to determine whether dietary Cr supplementation affects muscle growth in gilthead seabream (Sparus aurata) juveniles. Fish were fed ad libitum for 69 days with diets containing three increasing levels of creatine monohydrate (2%, 5% and 8%) that were compared to a non-supplemented control (CTRL) diet. At the end of the trial, the fast-twist skeletal muscle growth dynamics (muscle cellularity) and the expression of muscle-related genes were evaluated. There was a general trend for Cr-fed fish to be larger and longer than those fed the CTRL, but no significant differences in daily growth index (DGI) were registered among dietary treatments. The dorsal cross-sectional muscle area (DMA) of fish fed Cr 5% and Cr 8% was significantly larger than that of fish fed CTRL. The groups supplemented with Cr systematically had a higher relative number of both small-sized (≤20 µm) and large-sized fibres (≥120µm). Dorsal total fibres number was highest in fish fed 5% Cr. In fish supplemented with 5% Cr, the relative expression of myogenic differentiation 1 (myod1) increased almost four times compared to those fed the CTRL diet. The relative expression of calpain 3 (capn3) was highest in fish fed diets with 2% Cr supplementation, but did not differ significantly from those fed the CTRL or Cr 5%. The myod1 gene expression had a positive and significant correlation with that of capn1, capns1a and capn3 expression. These results suggest that the observed modulation of gene expression was not enough to produce a significant alteration in muscle phenotype under the tested conditions, as a non-significant increase in muscle fibre diameter and higher total number of fibre was observed, but still resulted in increased DMA. Additional studies may be required in order to better clarify the effect of dietary Cr supplementation in fish, possibly in conjunction with induced resistance training.